Comparative analysis of Proximate and Anti-fungal Activities on Palm Oil Treated Ash Extracts of Musa sapientum and Musa paradisiaca Peels collected from Local Market in Akwa Ibom State, Southern Nigeria - I. D. Uffia; O. E. Udofia; M. E. Bassey; R. O. Esen; E. J. Egong; O. D. Akan (Journal of Applied Sciences and Environmental Management)
Extracts from banana and plantain parts (flowers, bracts, ripe, unripe fruits, leaves, and stems) have bioactive constituents used as therapies for different human ailments. Although similar in growing on large herbs, elongated leaves, and producing edible fruits, they differ in taste and need for processing. This study used standard methods to evaluate differences due to palm oil treatment on the proximate and anti-fungal activities of ash extract of Musa sapientum and Musa paradisiaca peels collected from local market in Akwa Ibom State, Southern Nigeria. Results show that the moisture content of banana (M. sapientum) peel ash extract was 1.68 ±0.001 and 1.34 ±0.002 % with and without palm oil treatment, respectively. Also, the moisture content of plantain (Musa paradisiaca) was 1.29 ±0.002 and 1.17 ±0.003 % with and without palm oil treatment, respectively. However, the crude fibre, ash, and protein contents of ash extracts (M. paradisiaca and M. sapientum) decreased (p <0.05) with a palm oil treatment. Conversely, palm oil amendment increased the ash extracts' lipid, carbohydrate, and energy values. Ash extracts (M, paradisiaca, and M. sapientum) increasingly inhibited the growth of typical palm oil fungal species in a concentration-dependent manner. Their anti-fungal activities show they could be used as natural food preservatives or therapeutic agents in fungal disease conditions.